Prospect of Graphene Interface Control for Tougher Ceramic Composites - Clegg Bill; Kendall Kevin (Journal of Advances in Nanotechnology, 2018)
Graphene-Ceramic Composites (GCCs) have been little studied compared to graphene-polymer composites 1. Recent reviews 23 indicate that both mechanical and electrical property ceramic improvements can be obtained by mixing small quantities, typically 1 to 15% of graphene material with a ceramic precursor, then compacting and sintering. The greatest effect is on the electrical properties. The electrical conductivity of a material was first shown to rise by several orders of magnitude for only a 1% volume addition of graphene as in polymer composites 4 but the stiffness, strength and toughness only increased by 20-160% or so at 5% addition, a rather minor improvement compared to significant increases caused by slight ceramic process changes. Some crack bridging and pull-out mechanism was observed by electron microscopy in graphene-alumina composites, though the effects were modest. Surface friction and wear improvements of around 100% were also notable. This paper seeks to show that much higher toughness increases might be produced using the method pioneered by Clegg et al 5, where the graphite interlayers are replaced with graphene to produce improved ordered interfaces with reliable coverage and consistent interface fracture energy, enabling an increase in the fracture resistance of the ceramic by two orders of magnitude.
Keywords: Graphene